Research Ethics for Students in the Social Sciences 2020
DOI: 10.1007/978-3-030-48415-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Confidentiality

Abstract: After Reading This Chapter, You Will: Know what confidentiality entails and why it is important in research Become familiar with techniques of securing confidentiality Understand the difference between anonymity and confidentiality Be able to identify breaches of confidentiality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It is important to emphasize that the students' names were kept confidential throughout the whole study. Bos (2020), stated that a crucial principle of confidentiality involves an obligation for the researcher to guarantee that any use of information obtained from or shared by human subjects respects the dignity and autonomy of the participant, and does not violate the interests of individuals.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to emphasize that the students' names were kept confidential throughout the whole study. Bos (2020), stated that a crucial principle of confidentiality involves an obligation for the researcher to guarantee that any use of information obtained from or shared by human subjects respects the dignity and autonomy of the participant, and does not violate the interests of individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Confidentiality was maintained for all research participants using processes developed from principles found in Bos (2020). Data were not linked to the participants' names or other identifying information.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we submit the research proposal to the ethics committee from the Universitas Surabaya to gain acknowledgement that this study meets the ethical standard to minimize harm and risks, including confidential survey and conflict of interest. Moreover, confidentiality entails a researcher's commitment to ensure that the collected information from human subjects respects the respondents' dignity and autonomy by making promises not to disclose personal data (Bos, 2020).…”
Section: Data Collectionmentioning
confidence: 99%